Biochemical and histological effects of sub-chronic exposure to atrazine in crayfish Cherax destructor - Stara, Alzbeta; Kouba, Antonin; Velisek, Josef (Chemico-biological interactions, 2018)
Atrazine (ATR) is a triazine herbicide banned in the European Union. It remains one of the most widely used herbicides in other parts of the world. Considering the scarcity of data on its possible harm to the environment and to human health, we assessed sub-chronic effects of a 14-day exposure at the environmentally relevant concentration of 6.86 μg/L and at 10% of the 96hLC50 (1.21 mg/L) in crayfish Cherax destructor and their recovery in a 14-day period in ATR-free water. Indicators assessed were behavior; hemolymph biochemical profile; oxidative and antioxidant parameters in gill, hepatopancreas, and muscle; and histology of gill and hepatopancreas. Crayfish exposed to the environmental concentration showed significant differences (P < 0.01) from controls in biochemical parameters of hemolymph (lactate, alkaline phosphatase) and activity of superoxide dismutase, as well as in histology of gill tissue. The higher concentration led to low motor activity, differences in biochemical profile of hemolymph (lactate, alkaline phosphatase, ammonia, glucose), antioxidant biomarkers (superoxide dismutase, catalase, glutathione reductase, glutathione S-transferase, reduced glutathione), as well as gill and hepatopancreas histology. Some observed effects persisted after 14-days recovery in ATR-free water. The results provide evidence that environmental concentrations of ATR produce negative effects on freshwater crayfish.
Keywords: atrazin; superoxiddismutasa; Superoxide Dismutase; Toxicity Tests, Chronic; antioxidancia; Glutathione Transferase; hemolymfa; Astacoidea; zvířata; Antioxidants; Atrazine; oxidační stres; Hepatopancreas; Hemolymph; severní raci; Oxidative Stress; biologické markery; testy chronické toxicity; Animals; vystavení vlivu životního prostředí; hepatopankreas; Gills; Environmental Exposure; Biomarkers; žábry; glutathiontransferasa